Performance evaluation of PV module using water filters and infrared reflective glass covers - Baradey, Y.; Hawlader, Mohammad Nurul Alam; Idres, Moumen; Ihsan, Sany Izan (2013)
The Photovoltaic (PV) system converts only a selected band (0.35μm to 0.82 μm) of solar radiation to electricity. The absorption of radiation outside this band leads to a temperature raise of PV module which affects its performance. Experiments were performed to prevent radiation outside the selected to reach the PV panel using water filtersand different types of infrared reflective pigments. The results of the experiments showed that the optimum water filter panel was the one with thickness of 10 mm. It led to about 4% improvement in the open circuit voltage of the module, and a significant reduction in the module’s average operating temperature up to 21oC. The optimum coated cover glass was 10 micron IRR glass cover which led to about 50% reduction in solar radiation, 22o In 1994, Beauchamp [6] used blue-red reflecting cover glasses to reduce the absorptance of infrared radiation in GaAs and amorphous solar cells. He found out that three percent of output power increased due to lowering the temperature of solar cells by using blue-red coated cover glasses. Sopian et al. [7] improved the thermal and the electrical efficiency of the thermal photovoltaic system by designing and testing a double pass air PV/T collector.Tripanagnostopoulos et al.[8] added thin flat metallic sheet (TFMS) in the middle of the air channel in the PV/T-air collector but its effect on the operating temperature of the photovoltaic cells was not significant.Russell et al.[9] conducted experiments on triple junction solar cell using Ultra violet reflective (UVR) and infrared reflective (IRR) coatings on glasses in order to reflect the ultraviolet and infrared radiation C reduction in the average temperature of the module, and 5.3% improvement in its open circuit voltage.